1988
DOI: 10.1530/jrf.0.0820697
|View full text |Cite
|
Sign up to set email alerts
|

Co-ordination of electrical activity in the myometrium of pregnant ewes

Abstract: Summary. The co-ordination of spontaneous and evoked electromyographic (EMG) activity was examined in the uterus of ewes from Day 100 of pregnancy and during labour. During pregnancy the onset of bursts of EMG activity was synchronous to within 2\p=n-\3min when recorded by electrodes at any recording site. Individual EMG spikes, whether occurring spontaneously or evoked by electrical stimulation of the myometrium, appeared to propagate between recording electrodes that were 1\p=n-\3cm apart, in the longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 13 publications
(16 reference statements)
1
31
0
1
Order By: Relevance
“…This phenomenon explains an anomaly (26) as to why spikes that propagate quite fast (in our case 7 cm/s) can take so long to travel relatively short distances (Figs. 8 and 9).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This phenomenon explains an anomaly (26) as to why spikes that propagate quite fast (in our case 7 cm/s) can take so long to travel relatively short distances (Figs. 8 and 9).…”
Section: Discussionmentioning
confidence: 71%
“…Another potential complication is the fact that gap junctions that electrically connect myometrial cells may form spontaneously in vitro, which may improve electrical coupling and affect electrical propagation (14,29). Finally, even if a stable pacemaker had been found, there is evidence to suggest that this may not be stable during longer recording periods (26). Nevertheless, this study provides information as to the electrical behavior of the pregnant uterus at term.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although suggestive of the presence of cells generating spontaneous potentials, this characteristic is not present in all impalements within the same preparation and tissue location (24). Parkington et al (28), in the ewe, could not find a consistent site for the initiation of myometrial bursts, even during labor. In the rat, several studies did find a tendency for the pacemaker to occur more frequently at the ovarial end of the horn (4, 9), which was also seen in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…The electrical activity in the uterus is characterized by bursts of spiking activity interspaced with periods of quiescence (6,16,19,25). Recordings with several to large numbers of extracellular electrodes have shown that these spikes (action potentials) propagate through the myometrium from cell to cell through the presence of gap junctions (10,11,26,28,35). There is also increasing evidence that electrical and contractile activity is quite limited during gestation but increases when term approaches to prepare for delivery (13,41).…”
mentioning
confidence: 99%